Pemanfaatan Lemon Sebagai Pengganti Rennet Pada Pembuatan Keju Mozarella dalam Bentuk Olahan Potato Cheese Ball - Arjuna Seva Aristya; Alip Suroto; Arinta Desti Larasati (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Mozzarella cheese is traditionally made using rennet, an enzyme derived from the stomach lining of ruminant animals that plays a key role in coagulating milk. While effective, rennet has certain limitations such as its limited availability, relatively high cost, and concerns among vegetarians and certain religious groups regarding its animal origin. As a result, alternative coagulants that are easier to obtain, plant-based, and more environmentally friendly have gained interest. One such natural ingredient is lemon juice, which contains citric acid and can mimic the coagulation effect of rennet. This study aims to explore the effectiveness of lemon juice as a rennet substitute in the production of mozzarella cheese, specifically when applied in a food product like cheese-stuffed potato balls. The research involved organoleptic testing by 30 panelists to evaluate five sensory aspects: color, aroma, taste, texture, and overall acceptance. Several formulations were tested, and the sample containing 20 ml of lemon juice, 2 grams of citric acid, and an additional herb mix (Sample C) was rated the highest in preference across most parameters. The findings suggest that lemon juice is a viable alternative to rennet in mozzarella cheese making, particularly for small-scale or home-based production. It not only delivers acceptable sensory qualities but is also more accessible and affordable. Moreover, using lemon juice supports the development of more sustainable and vegetarian-friendly food options. In conclusion, lemon juice can successfully replace animal-based rennet, making mozzarella cheese production more inclusive, cost-effective, and environmentally conscious.